Evaluating Real Estate Equities in the Nigerian Stock Exchange: Trends, Risks, and Market Performance - Misbahu Falaki Abdulkadir; Sani Inusa Milala (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2025)
The real estate sector is a vital component of the Nigerian economy, with listed equities providing a critical avenue for investment. The performance of these equities is influenced by a complex interplay of macroeconomic forces, global shocks, and emerging sector-specific trends such as sustainable finance and technological adoption. Existing research on Nigerian real estate has often focused on direct property performance or isolated factors, leaving a gap in the holistic understanding of the listed equity segment. A consolidated analysis that integrates traditional macroeconomic drivers with contemporary influences like green financing and digitalization is lacking. This study is necessary to provide investors, policymakers, and corporate managers with a comprehensive, evidence-based framework for understanding the evolving risk-return profile of real estate equities in Nigeria, thereby supporting more informed investment and strategic decisions. This research aims to holistically evaluate the performance of real estate equities on the Nigerian Stock Exchange by identifying historical trends, assessing key risks, and analysing the impact of both traditional and modern performance drivers from 2014 to 2024. The study employed a quantitative research design, utilizing secondary data from the Nigerian Exchange Group and the Central Bank of Nigeria. A longitudinal analysis was conducted, followed by a panel regression model to examine the relationships between equity performance and independent variables including macroeconomic indicators, green finance flows, and technology adoption proxies. The analysis revealed that real estate equities provided an average annual return of 7.1% but with high volatility (Standard Deviation of 18.5%). Inflation and interest rates showed a significant negative impact on returns (β = -0.45 and β = -0.32, p < 0.05, respectively). A "green premium" was identified, with firms engaged in sustainable projects outperforming peers by 5%. Furthermore, a strong positive correlation was found between technology adoption and revenue growth (r = 0.60). The sector exhibited a high Beta of 1.15, indicating greater volatility than the broader market. In Conclusion the study concludes that the performance of Nigerian real estate equities is dictated by a combination of persistent macroeconomic sensitivities and powerful emerging trends. For the sector to achieve sustainable growth, a multi-stakeholder approach is required, where investors strategically allocate capital, firms integrate sustainability and technology into their core strategies, and policymakers enhance supportive regulatory frameworks.